Bridging Between Financial Performance and Government Performance: The Role of Public Sector Accounting in Realizing Good Governance - Setyawan, Wahyu (Oikonomia : Journal of Management Economics and Accounting, 2025)
Public sector accounting plays an important role in promoting transparency and accountability in modern governance. The implementation of an accrual-based accounting system, as mandated by the International Public Sector Accounting Standards (IPSAS), results in more accurate and relevant financial information. This system allows for the complete recording of assets and liabilities, thereby improving the efficiency of budget management. In addition, the integration of independent audits and technology-based supervision is a strategic step to prevent corruption and budget abuse. Implementation challenges, such as limited human resources and infrastructure, can be overcome through training, institutional strengthening, and technological innovation. Furthermore, public sector accounting contributes to sustainable development through reporting that covers financial, social, and environmental aspects. The integration of Sustainable Development Goals (SDGs) into financial reporting promotes inclusive and results-oriented decision-making. However, barriers such as a lack of understanding of sustainability concepts and policy incompatibilities require a collaborative approach across sectors. By adopting an integrated reporting framework, public sector accounting becomes a strategic instrument in realizing good governance and building public trust in government.